[TEX]A=1-\frac{3}{4}+\left (\frac{3}{4} \right )^2-\left ( \frac{3}{4} \right )^3+....-\left (\frac{3}{4} \right )^{2009}+\left ( \frac{3}{4} \right )^{2010}[/TEX]
[TEX]\frac{3}{4}A=\frac{3}{4}-\left (\frac{3}{4} \right )^2+\left ( \frac{3}{4} \right )^3+....-\left (\frac{3}{4} \right )^{2010}-\left ( \frac{3}{4} \right )^{2011}[/TEX]
[TEX]\frac{3}{4}A+A=1-\frac{3}{4}+\left (\frac{3}{4} \right )^2-\left ( \frac{3}{4} \right )^3+....-\left (\frac{3}{4} \right )^{2009}+\left ( \frac{3}{4} \right )^{2010}+\frac{3}{4}-\left (\frac{3}{4} \right )^2+\left ( \frac{3}{4} \right )^3+....-\left (\frac{3}{4} \right )^{2010}-\left ( \frac{3}{4} \right )^{2011}[/TEX]
[TEX]\frac{7}{4}A=1+\left (\frac{3}{4} \right )^{2011} \Rightarrow A=\frac{4}{7}\left [ 1+\left (\frac{3}{4} \right )^{2011} \right ][/TEX]
[TEX]\Leftrightarrow \left{\begin{A>0}\\{A<1}[/TEX] [TEX]\Leftrightarrow 0<A<1 \Rightarrow [/TEX] A không phải là số nguyên